SPATIAL ANALYSIS OF THE CRITICAL RATE LAND WITH A POVERTY RATE OF THE POPULATION IN GLAGAH SUB-WATERSHED - Wuryanto, Wuryanto (Universitas Negeri Semarang, 2017)
Glagah Sub-Watershed is part Bogowonto watershed located in Purworejo, Regency. Intention of writing about the relationship Spatial Analysis criticality land level with local people's poverty rate is the critical level of watersheds determine the relationship and the level of poverty in Sub-watershed Glagah. The aim is to know about the spatial distribution of the land critical level and poverty in sub-watersheds Glagah and evaluate land level of critical subzone Glagah and its relationship with the population poverty level.Research methodology for critical area analysis is based on Regulation Director General of Watershed Management and Social Forestry No. P.4 / V-SET /2013 on Technical Guidelines for Preparation of Spatial Data Wasteland. Basically, the techniques used in spatial analysis is the overlay method or overlaying and checks or direct surveys in the field.The distribution of the critical level of land in the study area is not critical (1532.04 ha), the critical potential (3986.11 ha), somewhat critical (1015.75 ha) and areas including critical land (6.37 ha), is the District Bener with total area of 30.95 hectares spread in the village Benowo (27.09 ha) and Kalitapas (3.861 ha), and the District Kaligesing (3.183 ha), located in the village Tlogobulu (3.183 ha) and a very high level of poverty population in the study area are in Kemejing 260 households (78.31%), Mudalrejo 215 households (34.62%), and Tepansari 181 households (44.80%).Factors that influence the degree of criticality of land in the study area is the village Benowo, Kalitapas and Tlogobulu is very steep slope and erosion hazard level, including very heavy. Distribution of degraded land are included on the mountain peak landform units andesite (S4) and eroded rocky hills andesite (S8). Poverty levels are very high in the village Mudalrejo, Kemejing and Tepansari are included in the District Loano and the critical level of land included in the category of critical potential, it shows that the criticality of land in the subzone Glagah not affected by poverty level. Critical land in subzone Glagah caused by severe erosion hazard level and the slope is very steep need for conservation action with silvopastoral agroforestry technique.Â Â